Peculiarities of interaction of the legal and political culture of student youth in the Republic of Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
The research topic is one of the topical problems at the present stage. We have been studying this topic for several years. The formation and development of political and legal culture of student youth directly affect the political system of society. The purpose of the study is to identify and analyze the specific features of the interaction of the legal and political culture of student youth in the Republic of Kazakhstan. The main idea of the article is to show the features of the legal and political culture of Kazakhstan’s student youth. The article analyzes the legal and political culture of student youth. The main ideas and proposals of the research can be used in the Kazakhstan science as an expert assessment. The results of the work can be used in the study of political culture and legal culture of student youth. In addition, the results of the work can be used by university students who study political science. The methodology of the work consists of theoretical and practical methods of research. Over a thousand students of higher educational institutions were interviewed in Kazakhstan and their level of legal and political culture was determined. Political views of the student youth of Kazakhstan were determined. The specifics of the interaction of legal and political culture of student youth of the Republic of Kazakhstan are substantiated.Key words: political culture, legal culture, electoral culture, student youth.